Crossing the line : racial passing in twentieth-century U.S. literature and culture - Wald, Gayle, 1965- (New Americanists., 2000)
Examines constructions of racial identity through the exploration of passing narratives including Black Like Me and forties jazz musician Mezz Mezzrow's memoir Really the Blues.